2014
DOI: 10.18388/abp.2014_1876
|View full text |Cite
|
Sign up to set email alerts
|

Hemagglutinin stalk domain from H5N1 strain as a potentially universal antigen.

Abstract: Influenza A virus infections are the major public health concern and cause significant morbidity and mortality each year worldwide. Vaccination is the main strategy of influenza epidemic prevention. However, seasonal vaccines induce strain-specific immunity and must be reformulated annually based on prediction of the strains that will circulate in the next season. Thus, it is essential to develop vaccines that would induce broad and persistent immunity to influenza viruses. Hemagglutinin is the major surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Recent trends in influenza vaccine development have followed two general paths: a universal vaccine approach using the stalk domain to induce a broad-spectrum neutralizing antibody, and a specific approach using VLPs [ 33 , 34 ]. In addition to their advantages of improved safety and strong immune response, VLP vaccines can readily substitute HA or NA genes to allow rapid, dynamic responses to a new influenza outbreak [ 14 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent trends in influenza vaccine development have followed two general paths: a universal vaccine approach using the stalk domain to induce a broad-spectrum neutralizing antibody, and a specific approach using VLPs [ 33 , 34 ]. In addition to their advantages of improved safety and strong immune response, VLP vaccines can readily substitute HA or NA genes to allow rapid, dynamic responses to a new influenza outbreak [ 14 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the development of a universal influenza vaccine relies on highly conserved regions of antigens [ 6 , 7 ], such as the stalk domain of the HA [ 8 , 9 ], the amino terminus of the M2 proteins (M2e or M2 ectodomain) [ 10 ] and the nucleoprotein (NP) [ 11 ]. Of note, phylogenetic analysis of virus strains isolated from different hosts indicates that the NP is relatively well conserved [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The globular head domain of HA plays a critical role in producing potent neutralizing antibodies, which indicates that HA can induce the production of neutralizing antibodies against only homologous viruses [ 1 77 ]. Therefore, many investigators demonstrated that highly conserved sequences such as the stem region of HA (called HA2 ) and M2e are more desirable targets for generating a universal vaccine [ 78 79 80 ]. Consist with the above results, our group also confirmed that the HA2 domain induced the production of a broad spectrum of neutralizing activities against different avian strains containing H5 subtypes (unpublished).…”
Section: Generation Of Novel Ai Vaccinesmentioning
confidence: 99%